Pengaruh Penerapan Sistem Akuntansi Keuangan Dan Kualitas Laporan Keuangan Terhadap Akuntabilitas Kinerja Instansi Pemerintahan (Studi Kasus Pada Badan Keuangan Aset Daerah Provinsi Sumatera Utara) - Masut, Masut; Dewi, Ika Puspita; Barus, Muhammad Joni (Universitas Islam Islam Sumatera Utara, 2023)
This study was conducted with the aim of testing whether the application of the financial accounting system and the quality of financial reports affect the accountability of government agency performance at the Regional Asset Finance Agency of North Sumatra Province both partially and simultaneously.The sample in this study were employees of the Accounting Division, Treasury and Regional Cash Division and Budget Management Division totaling 60 employees. The methods used in this research are descriptive statistical analysis, data quality test with validity and reliability test,classical assumption test with normality, heteroscedasticity and multicolonierity test, multiple linear regression analysis and hypothesis testing with t test, F test and coefficient of determination. The results of the study state that the application of the financial accounting system partially has a positive and significant effect on the accountability of government agency performance, the quality of financial reports partially has a positive and significant effect on the accountability of government agency performance, the application of the financial accounting system and the quality of financial reports simultaneously has a positive and significant effect on the accountability of government agency performance at the Regional Asset Finance Agency of North Sumatra Province..